THE EFFECT OF FOREIGN DEBT, FOREIGN DIRECT INVESTMENT, AND INFLATION ON ECONOMIC GROWTH IN 7 ASEAN COUNTRIES FOR THE PERIOD 2012-2020 - Yuliana, Shella; Aida, Neli; Ratih Taher, Arivina; Suparta, I Wayan (The Islamic Education and Multiculturalism Foundation, 2023)
This study intends to conduct empirical testing related to the effect of foreign debt, foreign direct investment, and inflation on economic growth in 7 ASEAN Countries during the period 2012-2020. The research method uses a quantitative approach with populations using Indonesia, Thailand, the Philippines, Myanmar, Vietnam, Laos, and Cambodia. The data analysis technique uses panel data regression with skunder research data type. The results showed that partially foreign debt had a negative and significant effect on economic growth. Meanwhile, foreign direct investment has a positive and significant effect on economic growth. Meanwhile, inflation also has a positive and significant effect on economic growth. However, simultaneously, foreign debt, foreign direct investment, and inflation affected economic growth in 7 ASEAN countries during the 2012-2020 period.